Company in Crisis - Lucia Vrablova; Milan Gregor (Communications - Scientific letters of the University of Zilina, 2011)
This paper deals with corporate crisis. It draws attention to the failing firm strategy in times of crisis. The corporate crisis is an important part of business life cycle. Proper crisis management is necessary for the survival of a competitive fight and staying on the market.